Sistem Pendidikan Islam pada Masa Kerajaan Mongol - Sultan; Rusman Paewai (CV. Creative Tugu Pena, 2024)
The main problem is what the Islamic education system was like during the Mongol empire. The aim of this research is to find out more deeply about the Islamic education system during Mongo's tenure. The research method used is a descriptive analysis approach which will provide an overview of the Islamic education system during the Mongol era. Data collection was carried out by exploring various references in the form of books, books, articles and other relevant scientific papers. The results obtained in this research are that the education system during the Mongol era consisted of three civilizations, namely the Changhari dynasty, the Golden Horde and the Khan Dynasty. Meanwhile, the condition of Islamic education consists of several categories, including: The movement of science centers, the growth of new sciences, the lack of Politikul Khanah, the number of schools and Mausu'at.